Silk Fibroin/Soursop Seed Bio-Adsorbent for Crystal Violet and Copper Metal Ion Removal - Lusi Ernawati; Ruri Agung Wahyuono; Abdul Halim; Nurul Widiastuti; Audi Sabrina; Kurnia Handayani (Journal of Engineering and Technological Sciences, 2022)
Groundwater highly contaminated with organic substances and heavy metal ions in the Kariangau Industrial Area, Balikpapan, East Kalimantan is indicated by the comparatively high COD. Therefore, the technology for treating wastewater to remove various toxins before releasing it into the environment needs to be advanced. Here, we present a green synthetic method of a composite adsorbent (SF/SS) using soursop seeds and silkworm cocoons. SEM, FTIR, and BET were used to analyze the physicochemical characteristics of the adsorbent. Mechanistic investigation of the SF/SS adsorbent performance for the removal of Cu2+ metal ions and crystal violet (CV) was conducted, while taking into account variables affecting adsorption properties. The Freundlich and Langmuir isotherm adsorption models were used to fit the adsorption equilibrium, while pseudo-first and second-order models were used to assess the adsorption kinetics. The mesoporous SF/SS adsorbent exhibited the highest adsorption capacities of 78.6 and 69.2 mg‧g-1, respectively. The pseudo-first model showed the best fit for CV removal with a kinetic rate of 0.0634 min-1, while the Freundlich model exhibited the best fitting for both of CV and Cu2+ removal. The results showed that SF/SS can be applied as an efficient adsorbent for both of heavy metal and organic dye removal.